Evaluation of Mammography Screening for Early Detection of Breast Cancer Among Women Attending St. Paul’s Hospital, Addis Ababa (2023) - Duol Dak Maluel; Solomon Zerihun; Bikila Merga Deresa; Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
In Ethiopia, breast cancer is the primary cause of death and the most common cancer among women worldwide. The purpose of this study was to evaluate how well mammography works for early breast cancer identification in women between the ages of 40 and 60. The study, conducted in Addis Ababa between April 20 and May 20, 2023, examined the opinions of 45 female patients who were purposefully selected to assess their knowledge of breast cancer and clinical breast examinations (CBE). The study combined primary and secondary sources in a quantitative research design. Women had CBE administered by a doctor, and then they had a mammogram to assess its efficacy in detecting breast cancer early. Participants were selected using a purposive sampling technique from St. Paul's Hospital, focusing on breast cancer patients who were receiving follow-up care and treatment at the facility. Data was collected through experiments and surveys, and descriptive statistical analysis was conducted using Excel and STATA software. The mean age of the 45 women who were screened was 51.02 years. 84.44% of participants had normal CBE results, while 73.33% of the women had negative mammogram results for breast cancer. Mammography is more useful for the early identification of breast cancer than CBE since it discovers more cases of the disease. The study's results, however, are constrained by its small sample size and narrow age range, which calls for more extensive and varied population-based research. The study's results, however, are constrained by its small sample size and narrow age range, which calls for more extensive and different population-based research. According to the study findings, 73.33% of respondents are not formally educated. It is a noteworthy discovery since it implies that a sizable portion of the population could not have access to or a chance to pursue an education.